2007
DOI: 10.1073/pnas.0702230104
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity from different SOD1 mutants dysregulates the complement system and the neuronal regenerative response in ALS motor neurons

Abstract: Global, age-dependent changes in gene expression from rodent models of inherited ALS caused by dominant mutations in superoxide-dismutase 1 (SOD1) were identified by using gene arrays and RNAs isolated from purified embryonic and adult motor neurons. Comparison of embryonic motor neurons expressing a dismutase active ALS-linked mutant SOD1 with those expressing comparable levels of wild-type SOD1 revealed the absence of mutant-induced mRNA changes. An age-dependent mRNA change that developed presymptomatically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
134
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 50 publications
10
134
0
1
Order By: Relevance
“…Although the L-serine level was also increased (Fig. 3C) consistent with a previous report (20), the D-/L-serine ratio was still higher in mSOD1 mice than in control mice (Fig. 3D).…”
supporting
confidence: 81%
“…Although the L-serine level was also increased (Fig. 3C) consistent with a previous report (20), the D-/L-serine ratio was still higher in mSOD1 mice than in control mice (Fig. 3D).…”
supporting
confidence: 81%
“…Glutamate action at AMPA receptors also induces SR and D-serine release from astrocytes (25). Interestingly, enzymes involved in D/L serine metabolism (e.g., phosphoserine phosphatase and 3-phosphoglycerate dehydrogenase) are among the earliest transcriptional changes detected in motor neurons in the G37R SOD1 mouse (26).…”
Section: Discussionmentioning
confidence: 99%
“…Values are means ± SEM. 3.7 who is heterozygous for the R199W mutation, using a peroxidase coupled method modified from Nagata et al (26). A rat spinal cord sample was also assayed in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in GM3 may also potentially slow disease by promoting oligodendrocyte differentiation (6), which is adversely affected in ALS mice (37), or by inhibiting the activation of matrix metalloproteinase-9 (38), which is expressed at high levels in those MNs most vulnerable in ALS (39). Interestingly, gene expression analysis studies carried out in ALS mice have shown that HEX (an enzyme that metabolizes GM2 to GM3) mRNA level is up-regulated in MNs before and during overt signs of disease (21,22). We confirmed these observations (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Last, patients with adultonset Tay-Sachs disease (GM2 gangliosidosis), a disease triggered by a deficiency in hexosaminidase (HEX), a lysosomal enzyme that hydrolyzes GM2 to GM3, have been reported in some instances to display a disease phenotype that closely mimics ALS (18)(19)(20). Interestingly, HEX mRNA is up-regulated within MNs of transgenic mice expressing the mutant human SOD1 protein (i.e., SOD1 G93A mice), a familial model of ALS (21,22). Collectively, these findings suggest that titration of GSLs is important to maintaining neuromuscular system homeostasis.…”
mentioning
confidence: 99%